PENGARUH TEKNIK DISKUSI TERHADAP SIKAP SOLIDARITAS PADA SISWA SMKN 4 MATARAM - Ummah, Rohmatul; Syarafuddin, H. M. (Realita : Jurnal Bimbingan dan Konseling, 2019)
Discussing is a guidance effort given to several individuals through group situations, with the target group being individuals who have the same problems so that students can help themselves in increasing their solidarity attitude. The formulation of the research problem is "Is There Influence of Discussion Techniques Against Solidarity Attitudes at XI grade Students of SMKN 4 Mataram in Academic Year 2018 / 2019". The purpose of the study was "Want to Know the Influence of Discussion Techniques Against Solidarity Attitudes at XI grade Students of SMKN 4 Mataram in Academic Year 2018 / 2019". Sampling technique used in this study is purposive sampling. The population in this study was 94 students, the sample used was 12 students. Data collection method used is questionnaire method as the main method and method of observation, interview and documentation as a complementary method. To analyze the data using the t-test formula, based on t count data analysis of 4.088 with t table value at 5% significance level with db (N-1) = 11 of 2.201. Thus the t count value is greater than the value of t in the table (4,088> 2,201), so it can be concluded that there is an Influence of Discussion Techniques Against Solidarity Attitudes at XI grade Students of SMKN 4 Mataram in Academic Year 2018 / 2019 is stated significant.